Lithiasis of upper biliary convergence - Misa, Carlos; Chinelli, Javier (Cirugía del Uruguay, 2019)
47 year old woman. 4 years ago simple cholangitis: common cystic-choledocian environment: Cholecystectomy and coledo-stomomy on Kehr tube. Since then, multiple admissions for "cholangitis to repeat" for what was done in total 7 ERCP. In all of them, a papillotomy was performed and biliary slime and purulent bile were obtained. In this admission, a Colangio Resonance is requested in which the cause of recurrent cholangitis is clearly observed: a 2 cm calculation. at the level of the upper bile confluence. A choledocholithotomy and latero-lateral choledochoduodenostomy is performed. Good post-operative evolution in arsenal of short bowel syndrome.